Amulet. Book eight, Supernova - Kibuishi, Kazu, 1978- (2018)
When Emily loses control of her Amulet, she is imprisoned in the Void, where she must escape the influence of the Voice, while her brother, Navin, travels to a space station where the Resistance is preparing to battle the approaching Shadow forces.
Sequel to: Firelight, book seven.
GN330L
Decoding demand: 91 (very high) Semantic demand: 100 (very high) Syntactic demand: 52 (medium) Structure demand: 87 (very high)
Keywords: Brothers and sisters -- Comic books, strips, etc; Amulets -- Comic books, strips, etc; Charms -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Imaginary places -- Comic books, strips, etc; Fantasy fiction; Graphic novels